LAPISAN PEMAHAMAN KONSEP MATEMATIKA DALAM SOAL PISA PADA SISWA SMA KELAS X - Risky Dwi Setyawati; Novisita Ratu (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This is a description qualitative research to describe the mathematic conceptual understanding layer in solving PISA questions for students in Grade X Senior High School. The research subjects are three students of Grade X MIPA 7 Negeri 1 State Senior High School Salatiga year of study 2018/ 2019, as the purposive sampling. Test and interview are used as the research data collection metodhs. The research results are for question number 1, Subject 1 reaches the level of formalising, Subject 2 reaches the level of investisingand Subject 3 reaches the level of observing. For question number , Subject 1 reaches the level image having, Subject 2 and 3 reaches the level of structuring. Next to question number 3, Subject 1 reaches the level of observing, Subject 2 reaches the level of investising and Subject 3 reaches the level of formalising.